Micro/nano technology systems for biomedical applications microfluidics, optics, and surface chemistry - Ho, Chih-Ming, Ph. D. (Oxford : Oxford University Press, 2010)
Providing a clear guide that moves from molecules through devices to systems, this book reviews fundamental aspects of microfluidic devices, including fabrication, surface property control, pressure-driven and electrokinetic flow, and functions such as fluid mixing, particle sorting and molecular separations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Biomedical engineering; Nanomedicine